2010
DOI: 10.1097/inf.0b013e3181daf921
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of H5N1 A/Vietnam/1194/2004 (Clade 1) AS03-Adjuvanted Prepandemic Candidate Influenza Vaccines in Children Aged 3 to 9 Years

Abstract: The results showed that 2 doses of AS03-adjuvanted H5N1 influenza vaccine at antigen-sparing doses of 1.9 microg or 3.75 microg HA elicited broad and persistent immune responses with acceptable reactogenicity, and without safety concerns, in children aged 3 to 9 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 22 publications
6
50
0
Order By: Relevance
“…However, previous studies have demonstrated that the 3.75 mg HA AS03 A -adjuvanted H5N1 vaccine elicited broad and persistent immune responses in elderly individuals and children. 18,19 Thus, this vaccine can be a suitable option for mitigating the morbidity and mortality of outbreaks and pandemics due to H5N1 and drifted strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have demonstrated that the 3.75 mg HA AS03 A -adjuvanted H5N1 vaccine elicited broad and persistent immune responses in elderly individuals and children. 18,19 Thus, this vaccine can be a suitable option for mitigating the morbidity and mortality of outbreaks and pandemics due to H5N1 and drifted strains.…”
Section: Discussionmentioning
confidence: 99%
“…The CMI profile observed in children 6-35 months of age was more typical for subjects naïve for H1N1, while that 30,31 There was no detectable effect of vaccination on the frequency of vaccine-specific CD8 + T-cells in either study, which is consistent with previous findings following influenza vaccination. 22,24 The results of both studies suggested that the AS03- The studies described in this manuscript were limited by their open-label design and by the absence of a control group. Moreover, they were not primarily designed to allow direct comparisons, and the results must be considered within the limitations of retrospective between-study evaluations.…”
Section: Discussionmentioning
confidence: 94%
“…In this manuscript, we report the results of two studies, which evaluated the persistence of 22 and eighteen months in adults. 23 As expected, a decrease in HI antibody GMTs was observed between Day 42 and Month 12 in both studies.…”
Section: Discussionmentioning
confidence: 98%
“…M72-specific CD4 þ and CD8 þ T cells expressing the immune markers IFN-g and/or IL-2 and/or TNF-a and/or CD40L were detected using a previously described method [17]. Briefly, undiluted whole blood was stimulated in vitro at 37 C with M72 peptides (15-mers overlapping by 11 amino acids; 1.25 mg/mL/ peptide; Eurogentec s.a.), medium (negative control) and positive control (staphylococcal enterotoxin B; 0.25 mg/mL; SigmaeAldrich) for 2 h in the presence of anti-CD28 and anti-CD49d antibodies.…”
Section: Cell-mediated Immune Responsesmentioning
confidence: 99%